Analisis Pendapatan dan Kelayakan Tumpang Sari Tanaman Kembang Kol dan Cabai Merah di Desa Swarna Dwipa Kecamatan Semende Darat Tengah Kabupaten Muara Enim - Harmudin, Gerut; Pusvita, Ema; Purwadi, Purwadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Agriculture plays an important role in the overall economy of Indonesia. This research examines the income analysis and feasibility of intercropping cauliflower and red chilies in Swarna Dwipa Village, Semende Darat Tengah District, Muara Enim Regency. The research method used is the case study method. Selection criteria for farmers who only use intercropping of cauliflower and red chilies. Data analysis uses data tabulation using income and business feasibility formulas. The results of this research are that the income obtained from intercropping of cauliflower and red chilies is IDR. 431,117,666.67 /ha/MT. Judging from the R/C comparison, intercropping of cauliflower and red chilies is suitable for sustainable cultivation, where the R/C value is 5.36. The BEP value of cauliflower at production costs is IDR 14,925,635/Ha/MT, and red chilies at a production cost of IDR 83,956,698/Ha/MT. Meanwhile, BEP production for each commodity is 1,866 kg/MT. The factors of land area, production quantity, selling price and place of sale influence the income and feasibility of intercropping farming.